A Case Of Malignant Melanoma in Pregnancy - Keating, Patrick J (Gezira Journal of Health Sciences, 2004)
This patient was a 33 year old, gravida 5, para 4, which is a little high in our country.  She had noticed a brown-pigmented mole on her leg, which she had had for about two years.  She had shown this to some healthcare workers, but they had reassured her.  At 17 weeks pregnancy it was becoming quite large and ulcerated and she was referred to see a plastic surgeon, who undertook an excisional biopsy and this confirmed the diagnosis of malignant melanoma.  There are various ways of classifying melanoma. The Breslow classification is thought to be the most prognostic, particularly for deeply invading lesions as this one was, measuring 6.2mm. This corresponds to Stage 2C, or Clarke’s level V. The real difficulty for us with this particular individual was that on the ultrasound scan there was a singleton pregnancy with a normal looking placenta and normal liquor, but there was a uterine mass, which had not been seen on the 11 week scan.  It was on the right side, it seemed to have the appearance of myometrium, it would possibly have passed for a rudimentary horn in a unicorunate uterus, but the concern clearly was that this was a metastisis from melanoma and that threw us into quite some difficulties deciding how to care for her.